Satisfaction Levels and Eating Behavior of Students at SMPN 2 Gondang Tulungagung Toward the Free Nutritious Meal Program (MBG) - Adhitya Rizky Arissaputra Aswanto; Prayitno Ribut Suwasono; Eunike Sri Puspaningsih; Juniarti Wulan Lestari; Novan Noviansyah (⁠International Journal of Sustainable Social Culture, Science Technology, Management, and Law Humanities, 2026)
The Free Nutritious Meal Program (MBG), launched nationally in January 2025 under Presidential Regulation No. 83 of 2024, is a government strategy to improve student nutrition and accelerate stunting reduction in Indonesia. This study aimed to describe student satisfaction levels and eating behavior patterns, and to analyze the relationship between satisfaction and students’ perceived eating behavior changes at SMPN 2 Gondang, Tulungagung. A quantitative cross-sectional design was employed with a single data collection point. Of 719 students (Grades VII–IX), 258 were selected via stratified random sampling (Slovin formula, e=5%): Grade VII n=90, Grade VIII n=87, Grade IX n=80. A structured questionnaire was used: Section B measured satisfaction across six domains (food taste/appearance, portion/adequacy, menu variety/nutrition, service/timeliness, hygiene/food safety, and overall satisfaction) using a 4-point Likert scale; Section C measured current eating behavior (C.1–C.4: meal frequency, vegetable/fruit intake, protein consumption, snacking habits) and students’ self-reported perception of behavior changes since joining MBG (C.5). Data were analyzed using descriptive statistics and Spearman correlation (α=0.05). Results showed 77.9% of students were satisfied overall (mean=3.07). Highest satisfaction was for hygiene/food safety (mean=3.42); lowest for menu variety (mean=2.71). Eating behavior was generally positive: 53.3% regularly had lunch every day and 50.2% always finished the protein served. Snacking habits and fruit consumption remained suboptimal. Students’ self-reported perceptions indicated positive behavior changes since MBG, most strongly for lunch regularity (mean=3.24). A moderate positive correlation was found between total satisfaction and perceived behavior change (r=0.41, p<0.001). Menu diversity improvement and local food adaptation are the primary areas requiring intervention.